The differential effect of two cereal foods on gut environment: a randomized, controlled, double-blind, parallel-group study - Yamauchi, Yohsuke; Masutomi, Hirofumi; Ishihara, Katsuyuki; Hartanto, Tenagy; Lee, Chol Gyu; Fukuda, Shinji (Frontiers in Nutrition, 2024)
Cereal-based foods such as fruit granola (FG) and corn flakes (CF) form part of a fiber-rich diet. Dietary fiber has a good effect on human health. However, changes in gut microbiota and intestinal immunity have not been investigated. We conducted a randomized, double-blind, placebo-controlled trial to investigate the effects of FG and CF intake on gut microbiota, metabolome, and the immune system. Subjects continuously consume CF or FG for 4 weeks. Stool samples, and questionnaires on defecation were collected before, 2 weeks after, and 4 weeks after intake. Gut microbiota was analyzed using 16S rRNA gene amplicon sequencing. Fecal metabolomes were analyzed using GC/MS and CE-TOF/MS. Fecal IgA was analyzed using ELISA. The defecation frequency after cereal based food intake was improved. The different cereal-based foods had different effects on gut microbiome. The increase in intestinal IgA levels was positively correlated with the relative abundance of Dialister and the Lachnospiraceae ND3007 group in CF and FG group, respectively.. SCFAs showed a positive correlation with Prevotella 9 in the FG group. This study showed that the supplement in dietary fiber contained in CF and FG improves bowel movements. CF and FG each had different effects on gut microbes, metabolites and different relationships between fecal IgA or SCFAs and gut microbiota.